A Prototype of a Volumetric Three‐Dimensional Display Based on Programmable Photo‐Activated Phosphorescence. (6th April 2020) - Wan, Shigang; Zhou, Hongqi; Lin, Jinxiong; Lu, Wei
Abstract: A proof‐of‐principle prototype of a volumetric 3D‐displaying system is demonstrated by utilizing the photo‐activated phosphorescence of two long‐lived phosphorescent metal‐porphyrins in dimethyl sulfoxide (DMSO), a photochemically deoxygenating solvent. The first phosphorescent sensitizer, Pt(TPBP), absorbs a light beam with a wavelength of 635 nm, and the sensitized singlet oxygen is scavenged by DMSO. The second phosphorescent emitter, Pt(OEP), absorbs a light beam with a wavelength of 532 nm and visibly phosphoresces only in the deoxygenated zone generated by the first sensitizer. The phosphorescent voxels, 3D images, and animations are well‐defined by the intersections of the 635‐nm and 532‐nm light beams that are programmable by tuning of the excitation‐power densities, the beam shapes, and the kinetics. As a pivotal selection rule for the phosphorescent molecular couple used in this 3D‐displaying system, their absorptions and emissions must be orthogonal to each other, so that they can be excited and addressed independently. Abstract : A solution for three dimensions : In a photochemically deoxygenating DMSO solution of two Pt II porphyrin complexes under air, volumetric three‐dimensional phosphorescent images and animations have been projected by intersecting two light‐beams with different wavelengths. This proof‐of‐principle 3D display is simple yet effective and displays a novel application of molecular phosphorescent materials.